[Rezension von: Markschies, Christoph Johannes, 1962-, Hellenisierung des Christentums : Sinn und Unsinn einer historischen Deutungskategorie] - O'Leary, Joseph Stephen (The journal of theological studies, 2013)
What has Berlin to do with Athens? For Christoph Markschies, who is one of the most imposing figures in Berlin today, and who mentions Berlin on almost every page, Hellenization refers primarily to a ‘modern research paradigm’ (p. 67) developed in Berlin at the start of the last century and being renewed according to a new model in Berlin today., The subtitle is quoted as referring to a ‘contested’ (umstritten) category (p. 16), but this has become ‘historical’ in the subtitle of the book as published. This last-minute change no doubt reflects awareness that, whereas the modalities, extent, and chronology of Hellenization have occasioned much historical debate in particular cases, the category itself has not been particularly controversial, which is why J. G.